Strategi Bertahan Hidup Keluarga Nelayan Tradisional Di Kelurahan Malabero: Perspektif Sosial-Ekonomi dan Solidaritas Komunitas - Hayati, Rohmah Nur; Heriyanti, Lesti; Djakfar, Ledyawati (Jurnal Community, 2024)
The fishing community of Bengkulu is well known for the lives of the poor. Poverty of fishing communities is a problem that should receive special attention and solutions so that fishing communities can survive. This research aims to determine the survival strategies of traditional fishing families in Malabero Village, whose daily work is only as traditional fishermen using small boats along with fishing gear and nets. This research will be conducted in Malabero Village, Teluk Segara District, Bengkulu City using a descriptive approach. The technique for determining informants used was purposive sampling, and the data collection techniques used were observation, interviews and documentation. The data analysis techniques used are according to Milles and Huberman, namely data reduction, data presentation, and drawing conclusions. The results of this research describe forms of active survival strategies for traditional fishing families, including mutual cooperation, making maximum use of natural resources by going to sea, and doing small-scale sales to help meet the family's needs. Even though fishermen's lives experience many obstacles and challenges, using these active strategies can help them meet their needs for survival. The emergence of these strategies is due to challenges and obstacles such as climate and weather changes, lack of technology and fishing equipment, and the relatively cheap price of fish on the market.